Some features of postmodernism, 24.-28.04.1989., IUC Dubrovnik, Croatia - Gjurgjan, Ljiljana Ina (1989)
The lecture has looked into the rhetorical figure of ekphrasis as understood by Hutcheon and its ideologcial implications in some postmodern texts.